Black Sands In The Pacific Mexican Littoral - Arturo Carranza Edwards (International Marine Minerals Society, 1994)
One hundred ninety nine beach face sand samples from an equal number of beaches from the Mexican Pacific were studied. Based on petrological and chemical analysis some locations have been studied in more detail. Black sands from the following areas are discussed: (1) west Baja California Peninsula, where black sands rich in magnetite and ilmenite have maximum values of 50% iron and 14% titanium in the very fine sand fraction; (2) east Gulf of California, in its northern portion, the black sands show maximum values of 43% iron and 5% titanium in the fraction 2 to 4 0;-(3) the south Mexican Pacific, characterized mainly by medium sands, moderately well sorted, show that the fine sand fractions reach values of 35% iron and 41% titanium. X-ray fluorescence applied on selected samples constituted by feldsarenites and lithic feldsarenties, showed the presence of rare elements in some of the studied samples.